SO2 and copper tolerance exhibit an evolutionary trade-off in Saccharomyces cerevisiae. - Cristobal A Onetto; Dariusz R Kutyna; Radka Kolouchova; Jane McCarthy; Anthony R Borneman; Simon A Schmidt (PLoS Genetics, 2023)
Copper tolerance and SO2 tolerance are two well-studied phenotypic traits of Saccharomyces cerevisiae. The genetic bases of these traits are the allelic expansion at the CUP1 locus and reciprocal translocation at the SSU1 locus, respectively. Previous work identified a negative association between SO2 and copper tolerance in S. cerevisiae wine yeasts. Here we probe the relationship between SO2 and copper tolerance and show that an increase in CUP1 copy number does not always impart copper tolerance in S. cerevisiae wine yeast. Bulk-segregant QTL analysis was used to identify variance at SSU1 as a causative factor in copper sensitivity, which was verified by reciprocal hemizygosity analysis in a strain carrying 20 copies of CUP1. Transcriptional and proteomic analysis demonstrated that SSU1 over-expression did not suppress CUP1 transcription or constrain protein production and provided evidence that SSU1 over-expression induced sulfur limitation during exposure to copper. Finally, an SSU1 over-expressing strain exhibited increased sensitivity to moderately elevated copper concentrations in sulfur-limited medium, demonstrating that SSU1 over-expression burdens the sulfate assimilation pathway. Over-expression of MET 3/14/16, genes upstream of H2S production in the sulfate assimilation pathway increased the production of SO2 and H2S but did not improve copper sensitivity in an SSU1 over-expressing background. We conclude that copper and SO2 tolerance are conditional traits in S. cerevisiae and provide evidence of the metabolic basis for their mutual exclusivity. These findings suggest an evolutionary driver for the extreme amplification of CUP1 observed in some yeasts.